Strategi Bertahan Pedagang Fashion di Era Digital (Studi pada Pasar Panorama Kota Bengkulu) - Etia Mardiyanti; Eka Sri Wahyuni; Yenti Sumarni (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2026)
This study aims to determine the survival strategies of fashion vendors in the digital era (a study of the Panorama Market in Bengkulu City) and the factors influencing business sustainability at the Panorama Market in Bengkulu City. This research is a field study using a descriptive qualitative approach. Data collection techniques were conducted through observation, interviews, and documentation, while data analysis techniques utilized data reduction, data presentation, and conclusion drawing. The results indicate that vendors' survival strategies include service, pricing, product, and digital promotion strategies. Some vendors still rely on direct sales, while others have begun utilizing social media as a promotional tool. Factors influencing business sustainability include internal factors, such as experience and business capabilities, and external factors, such as technological developments and business competition. Thus, vendors' survival strategies are implemented through a combination of conventional strategies and the gradual adoption of igital technology